2014
DOI: 10.1016/j.jare.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of ZrO2/Al2O3-montmorillonite composite as catalyst for phenol hydroxylation

Abstract: Zirconium dispersed in aluminum-pillared montmorillonite was prepared as a catalyst for phenol hydroxylation. The effects of varying the Zr content on the catalyst’s physicochemical character and activity were studied with XRD, BET surface area analysis, surface acidity measurements and scanning electron microscopy before investigating the performance for phenol conversion. The zirconia dispersion significantly affects the specific surface area, the total surface acidity and surface acidity distribution relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…However, there is little report on improving catechol selectivity alone. The modified zeolite, composite metal oxide, organic metal complex and molecular sieve catalysts are used in the catalytic hydroxylation of phenol . However, only 60% of phenol conversion and 85% of catechol selectivity were obtained over these catalysts .…”
Section: Introductionmentioning
confidence: 99%
“…However, there is little report on improving catechol selectivity alone. The modified zeolite, composite metal oxide, organic metal complex and molecular sieve catalysts are used in the catalytic hydroxylation of phenol . However, only 60% of phenol conversion and 85% of catechol selectivity were obtained over these catalysts .…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that the loading of the ZrO 2 nanoparticles onto porous material like Al 2 O 3 (activated alumina, a lower cost commercial support with large surface area) is an effective method to increase the photocatalystic activity and chemical stability even at low pHs . Several methods have been applied for synthesis of Al 2 O 3 /ZrO 2 composites, such as solvothermal method, hydrothermal method, combustion, and sol–gel method . Among them, sol‐gel method is of great interest for preparing nanoparticles, due to its the low‐temperature process, environmental friendly and economic feasibility…”
Section: Introductionmentioning
confidence: 99%
“…us, it is very important to select a suitable catalyst for phenol hydroxylation. e catalysts for phenol hydroxylation include modified molecular sieves, composite metal oxides, organic metal complexes, etc [7][8][9]. It has been reported that the phenol conversion of these catalysts for phenol hydroxylation was usually between 40% and 60%, and the catechol selectivity was seldom more than 75% [10][11][12].…”
Section: Introductionmentioning
confidence: 99%